Model of radial leakages with circulation in single-threaded screw extruders - Slavnov, Evgeniy Vladimirovich; Sudakov, Andrey Ivanovich; Buzmakova, Svetlana Vladimirovna (Computational Continuum Mechanics, 2008)
A new model of leakages through the radial clearance in single-threaded screw extruders is proposed. The weakness of the existing models is that the leakage flow is carried outside the boundaries of the channel and does not participate in the flow any longer, although in real conditions the material migrates from one flight of the extruder channel to the other conjugated via the flight land. The general idea of the approach and its main distinguishing feature are as follows. In simulation of the channel flow, the balance of mass discharges through the main channel and clearance is expressed as an additional differential relationship, and the intensity of the leakage flow, with consideration of pressure distribution throughout the channel length, is defined by the functional dependence with the delayed argument. An example problem on the isothermal flow of linear viscous flow fluid in the straight - flow extruder has been solved to examine the influence of radial clearance, angle of rifling and the width of flight on the integral characteristics of the process. The surfaces of flow stability boundary in the screw channel are constructed.